THE ROLE OF CREATIVE MANAGEMENT IN THE DEVELOPMENT OF INNOVATIVE PROJECTS - DESYATOV, Tymofii; DEREVIANKO, Denys; BALABA, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the relationship between creative management and the processes of establishment and implementation of innovative activities by enterprises. Creative management involves the introduction of modern tools, updating the management system, transition to the active use of technologies and other things necessary for the development of innovative projects. Accordingly, creative management forms the basic foundations for the development of innovative ideas that are embedded in relevant projects and implemented due to the originality of management decisions. The importance of adhering to the principles of creativity and innovation when modernizing the management system is emphasized, as a result of which enterprises are able to carry out high-quality design and strategizing of new areas of activity. The main factors that change the meaning of creative management are the development of means of production, scientific and technical progress, improvement of equipment and technology, the worker with his abilities and skills will continue to be the main element of production, but the meaning of work is changing. Attention was drawn to the importance of developing and implementing a program of creative management of the development of innovative projects, focusing in particular on the method of step-by-step management. A number of challenges are identified that can weaken the role of creative management in the context of setting up innovative activities by enterprises. The vectors of creative management in the context of the development of innovative projects are defined. Creativity and innovation have common implementation vectors, because they are focused on the invention of completely new business ideas, the implementation of which allows the enterprise to significantly cover the competitive position on the market and ensure the renewal of resource provision. A step-by-step model of ensuring the creativity of work in the context of the development of innovative projects has been formed.
Keywords: creative management; innovative projects; innovative activity; creativity; innovativeness